Effects of biopolymers, cork, and Rhizobium tropici-derived extracellular polymeric substances on soil microbial communities - Craft, Alexis K.; Karapareddy, Sowndarya; Anche, Varsha C.; Janga, Madhusudhana R.; Soyinka, Obaloluwa; Sanathanam, Sravan K.; Nyaku, Seloame T.; Sharma, Govind C.; Senwo, Zachary; Sripathi, Venkateswara R. (Frontiers in Microbiomes, 2025)
IntroductionSoil microorganisms play a crucial role in plant development, while biopolymers, such as cork and Extracellular Polymeric Substances/Exopolysaccharides (EPS), can enhance soil health. However, these amendments may affect DNA extraction and microbial analysis, necessitating the validation of the extraction method before conducting next-generation sequencing (NGS).MethodsThis study evaluated 48 soil samples from Decatur, Alabama (Silt loam) that underwent four treatments: unamended soil (soil.control), soil with cork (soil.cork), soil with EPS (soil.EPS), and soil with both cork and EPS (soil.cork.EPS). Samples were collected at four time intervals (0-, 24-, 48-, and 72-hours post-treatment), with three biological replicates for each treatment. The FastDNA Spin Kit proved the most effective among the six DNA extraction methods tested.Results and discussionAmplicon sequencing of the 16S rRNA gene identified 62,996 amplicon sequence variants (ASVs), with 513 ASVs shared across all time points and 467 ASVs shared among the different treatments. The microbial community was primarily composed of Actinobacteria, Proteobacteria, and Acidobacteria, with Actinobacteria being the most abundant phylum. Actinobacteria, Alphaproteobacteria, Bacilli, and Betaproteobacteria contributed to microbial diversity at the class level. Notable families such as Bacillaceae, Gaiellaceae, Micromonosporaceae, and Streptomycetaceae showed treatment-dependent variations. Core microbiome analysis revealed Bacillus and Gaiella as the dominant genera, which play vital roles in soil ecosystem stability and nutrient cycling. These microbes contribute to carbon sequestration, nitrogen fixation, and phosphorus solubilization, improving soil fertility and plant-microbe interactions. These findings offer valuable insights into microbial dynamics in amended soils, providing information that can improve soil quality and agricultural productivity.